RJ: a Java package providing JR‐like concurrent programming. (6th May 2015) - Olsson, Ronald A.; Williamson, Todd
Summary: The JR concurrent programming language extends Java with a richer concurrency model, by adding several new types and statements. JR provides dynamic remote virtual machine creation, dynamic remote object creation, remote method invocation, dynamic process creation, rendezvous, asynchronous message passing, semaphores, concurrent invocation, and shared variables. This paper presents RJ, a package for Java that provides JR‐like features. The paper gives an overview of RJ and its key features; describes the implications of RJ's design, including how RJ provides additional, useful flexibility; discusses the implementation of RJ; and gives qualitative and quantitative evaluations of our work with respect to feasibility and usability, experimentation, migration, and performance. RJ has been successful in meeting these goals and in providing insight into the trade‐offs between using a concurrent programming language versus using the equivalent concurrent package. Our work has yielded a few surprises in dealing with some concurrent programming language features, in understanding the run‐time performances of JR versus RJ programs, and in obtaining some additional, useful flexibility for concurrent programming applications. Copyright © 2015 John Wiley & Sons, Ltd.